Outcomes of the environmental streamlining pilot projects. - Bracaglia, Frank; National Research Council (U.S.). Transportation Research Board; National Cooperative Highway Research Program; Vanasse Hangen Brustlin, Inc. (Washington, D.C. Transportation Research Board, 2005)
"This digest presents the results of NCHRP Project 25-24,, "Monitoring, analyzing, and reporting on the environmental streamlining pilot projects." The study was conducted by Vanasse Hangen Brustlin, Inc. the Principal Investigator was Frank Bracaglia."
Caption title.
At head of title: National Cooperative Highway Research Program.
"November 2005."
Also available online via the TRB publications website (http://www4.trb.org/trb/onlinepubs.nsf).
Keywords: Environmental impact analysis -- United States; Transportation -- Planning -- Environmental aspects -- United States